Magnetic adsorbents for selective removal of selenite from contaminated water. Issue 13 (2nd September 2019) - Evans, Samuel F.; Ivancevic, Marko R.; Yan, Jiaqiang; Naskar, Amit K.; Levine, Alan M.; Lee, Richard J.; Tsouris, Costas; Paranthaman, M. Parans
ABSTRACT: Novel meso- and microporous tire-derived carbon framework as a support for magnetic iron oxide nanoparticle adsorbents (MNA) that selectively adsorb selenite (Se(IV)) ions from contaminated water has been developed. Carbon-supported magnetic nanoparticle adsorbents (C-MNA) displayed higher adsorption values compared to MNA from 5 to 50 ppm selenite concentrations, maximizing at 48 ± 5 mg/g capacity with >99% Se removal at pH 3 and 5, and outperforms MNA at pH 7. These improvements will expand the range of water sources that can be treated, as well as easing adsorbent collection through magnetic separation.